Kinetics and Thermodynamic Study for Adsorption of Methylene Blue onto Mulberry Tree (Morus nigra L) Roots Powder - Mansour Faraj; Mohamed Erhayem; Ragwan Mohamed (Journal of Pure & Applied Sciences, 2019)
In this research, the batch adsorption models were conducted for the adsorption of Methylene Blue (MB) onto grounded Morus Nigra L roots powder (MNLRP) surface. Different adsorption parameters were applied in order to study the adsorption processes at 25, 35 and 45°C. Adsorption kinetics data were modeled with different kinetic models and the results revealed that the pseudo-second order model was the best fitting model. The results from thermodynamic parameters showed that the adsorption process was spontaneous and endothermic processes. The parameters values of standard free energy (?G0) were -1.730, -2.124 and -2.234 KJ/mol at 25, 35 and 45°C, respectively. The values of change standard enthalpy (?H0) is 12.6 KJ/mol and the values of change standard entropy (?S0) is 59.4 J/mol K. The randomness was increased at the solid/liquid interface. The findings in this study that the MNLRP could be used to remove MB dyes from aqueous solutions.